Penerapan Terapi Aktivitas Kelompok Pada Pasien Dengan Resiko Perilaku Kekerasan: Di Rumah Sakit Jiwa - hesti diana oktavia; Made Suastrawan; Ni Made Dwi Yunica Astriani (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2020)
Violent or aggressive behavior is a form of behavior that aims to hurt someone physically and psychologically. The aim of the authors is to determine the application of group activity therapy (TAK) stimulation of perception of the client's ability to control violent behavior. The method used by the author is a descriptive method with exposure to case studies through nursing care approaches namely assessment, enforcement of nursing diagnoses, planning, implementation, and evaluation of nursing. The application of group activity therapy is done 2 times a meeting with clients with RPK is to provide group activity therapy (TAK) stimulation of perception with five sessions namely Recognizing the usual Violent Behavior, Preventing Physical Violence Behavior, Preventing Social Violence Behavior, Preventing Violent Behavior and Preventing Violent Behavior and Preventing Violent Behavior by Obediently Taking Drugs. The problem of perception disorder is partially resolved so that it requires further treatment and collaboration with other medical teams, clients and families for the successful application of therapeutic activities to the perception stimulation group to control violent behavior.